PEMANFAATAN STRATEGI PERMODELAN UNTUK MENINGKATKAN KEMAMPUAN MEMBAWAKAN ACARA PADA SISWA KELAS VIII SMP UTAMA 1 BANDAR LAMPUNG - Rauhati, Rauhati (Lentera: Jurnal Ilmiah Kependidikan, 2015)
Indonesian should be a very enjoyable lesson, but in reality, specifically for basic competence hosted the value obtained by the students is still very low, students are less interested, unmotivated, and many students who lack the confidence to perform actively in bringing the show. This study aims to improve the process and learning outcomes on the basis of competence hosted by the language properly and mannered by using modeling strategiesThis study was conducted by two cycles, each cycle consisting of planning, action, observation and reflection. In the first cycle of learning hosted students are grouped by 5 members of the student and is represented by one member to perform present and how to bring the show on the second cycle of learning hosted students who performed best in the first cycle as a model for the members of his motivation in order to dare to appear in individuals to obtain the value of the individual. To find out upgrades hosted then use observation techniques. Aspects observed in each cycle is the activity of students and teachers and the learning process.Results of the analysis of the data shows there has been a increase in activity and learning outcomes of students from cycle to cycle. In the first cycle 36% of students still scored below the KKM, and on the second cycle increased to 92% of students had reached KKM. In the first cycle students completed totaling 16 students (64%) and students who have not completed 9 students (36%), while in the second cycle students completed totaling 23 students (92%) and who have not completed two students (8%). The percentage of completeness of students in the second cycle increased 28% from the results of tests in the first cycle is the percentage of 64% to 92%. Ketidaktuntasan percentage of students in the second cycle decreased by 28%. Based on the second cycle indicators that the strategy applied modeling can motivate students to dare to appear as presenters, which in turn can improve the ability of pupils and students get good grades.